Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.15829/1560-4071-2016-2-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Persistant Post-Operation Cognitive Dysfunction in 2 Type Diabetes Patients After Coronary Bypass Grafting

Abstract: Цель. Изучение предикторов стойкой послеоперационной когнитивной дис-функции (ПОКд) у пациентов с сахарным диабетом (Сд) 2-го типа, перенес-ших коронарное шунтирование (КШ) в условиях искусственного кровообраще-ния (ИК). Материал и методы. В исследование включено 54 пациента-мужчины с Сд 2-го типа, перенесших плановое КШ в условиях ИК, в возрасте от 45 до 69 лет. Всем пациентам помимо стандартного клинического обследования, проводи-лось нейрофизиологическое тестирование за 3-5 дней до операции, на 7-14-е сутки… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Importantly, angiotensin-converting enzyme (ACE) inhibitors, beta-blockers, and calcium antagonists did not show any significant correlations with the outcomes followed CABG [78]. However, there are available data on beneficial effects of statins on reducing the incidence of atrial fibrillation and cognitive impairment after CABG, including patients with diabetes mellitus [48,78].…”
Section: Comprehensive Risk Factor Control In Diabetic Patients In Comentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, angiotensin-converting enzyme (ACE) inhibitors, beta-blockers, and calcium antagonists did not show any significant correlations with the outcomes followed CABG [78]. However, there are available data on beneficial effects of statins on reducing the incidence of atrial fibrillation and cognitive impairment after CABG, including patients with diabetes mellitus [48,78].…”
Section: Comprehensive Risk Factor Control In Diabetic Patients In Comentioning
confidence: 99%
“…Diabetic patients showed higher endothelial activation and lower antiinflammatory response to CPB compared to non-diabetics [46]. Chronic hyperglycemia can lead to the central nervous system injury, resulting in diabetic encephalopathy with the onset of mild and moderate cognitive disorders [48]. Bruce et al found that 64% of diabetic patients with coronary artery disease had cognitive or emotional disorders [49].…”
Section: Diabetes-specific Risk Factors For Adverse Prognosis In Coromentioning
confidence: 99%
“…У больных СД отмечается и более высокая эндотелиальная активация и низкая антивоспалительная реакция при операции КШ с искусственным кровообращением по сравнению с больными без СД [42]. Хроническая гипергликемия приводит к повреждению ЦНС и формированию диабетической энцефалопатии с формированием легких и умеренных когнитивных расстройств [44]. Bruce D. G. обнаружил, что 64% пациентов с СД и ИБС имеют когнитивные или эмоциональные расстройства [45].…”
Section: характерные для диабета факторы риска неблагоприятного прогнunclassified
“…У больных КШ высокая вариабельность гликемии ассоциирована с риском послеоперационных осложнений. Высвобождение катехоламинов в ответ на гипогликемию сопровождается также снижением уровня калия плазмы, что приводит к удлинению интервала QT на ЭКГ, нарушению процессов реполяризации миокарда и может спровоцировать возникновение аритмий, в том числе ФП [44].…”
Section: характерные для диабета факторы риска неблагоприятного прогнunclassified